MAX share this! Vote for us! Analysis of pre-election Facebook communication and audience reactions of Latvia’s populist party KPV LV leader Aldis Gobzems - Rozukalne, Anda (Information & Media, 2020)
This article analyses the communication content by the Latvian populistic party KPV LV (LETA; Re: Baltica) and the audience’s reaction, with a focus on the daily updates and live videos that were posted on Facebook (FB) prior to the 13th elections of the Saeima (Parliament of Latvia). The aim of the research is to determine the type of populism that KPV LV employed (de Wreese, 2018).The research data was collected during the pre-election period in August – September 2018, when the popularity and social media activity of the party increased. The methods employed were qualitative and quantitative content analysis. In order to identify the structure of emotions expressed in audience-created content, the online data analysis tool “Emotion Recognition Model” was used. Given that populist ideology manifests itself in specific discursive patterns (Kriesi, Papas, 2015), the data interpretation was based on theoretical findings about populism as a political communication style (Jagers, Walgrave, 2007). In order to analyze the interrelations between populist communication and its audience, this study employed theoretical literature on social media use in populist communication and on expressions of emotions in social networking sites.
Keywords: populist communication; Facebook; social media audience engagement; emotions; Latvia